Hydroxymethylfurfural content and physicochemical properties of the caramel samples enriched with different dietary fibres - Dogan, M.; Toker, O. S. (CODON PUBLICATIONS, 2015)
Caramel is widely used in foods such as ice cream, biscuits, cake, chocolate and chocolate sauce, etc. Some toxic compounds like hydroxymethylfurfural (HMF) are formed during production of caramel. Therefore, decrease of HMF content of the caramel is important for human health. In the present study, different dietary fibres (inulin types, wheat, apple, lemon, pea and oat fibres) were added to the caramel formulation to reduce HMF content. In addition to the HMF content of the model caramel samples, physicochemical properties such as colour, pH, brix and a(w) values of the samples were determined. Both of the HMF content and physicochemical properties were significantly affected by fibre addition (P<0.05). High performance (HP) and high performance for high temperature process (HPX) type inulins were convenient for incorporation when considering the HMF content and colour properties of the samples. Principal component analysis was also applied to correlate variables. PC1 and PC2 explained approximately 85.58% of the variation in the data set. According to the result of this study, HP and HPX inulin samples might be added to caramel formulation or acid and sugar containing products to decrease HMF content.
Keywords: principal component analysis; sugar; acid; caramelisation; HMF; MAILLARD REACTION-PRODUCT; ABERRANT CRYPT FOCI; D-FRUCTOSE; 5-HYDROXYMETHYLFURFURAL HMF; THERMAL-DEGRADATION; SUCROSE; STORAGE; TEMPERATURE; MECHANISM; INCREASE; Food Science & Technology